Contribution of asparagine 346 residue to the carbapenemase activity of CMY‐2 β‐lactamase. Issue 2 (1st July 2013) - Dahyot, Sandrine; Broutin, Isabelle; de, Christophe; Guillon, Hélène; Mammeri, Hedi
Abstract Only a few plasmid‐borne AmpC (pAmpC) β‐lactamases, such as CMY‐2, can account for carbapenem resistance in Enterobacteriaceae in combination with outer membrane impermeability. The aim of this study was to elucidate the contribution of Asn‐346, which is well conserved among carbapenem‐hydrolyzing pAmpCs, to the hydrolysis spectrum of CMY‐2. Site‐directed mutagenesis experiments were carried out to replace Asn‐346 with glycine, alanine, valine, glutamate, aspartate, serine, threonine, glutamine, tyrosine, isoleucine, lysine, and histidine. The recombinant plasmids were transferred into wild‐type and porin‐deficient Escherichia coli strains. Asn‐346 replacement reduced significantly the MICs of all β‐lactams, except the Asn‐346‐Ile substitution that increased the MICs of cephalosporins, whereas it decreased those of carbapenems. The biochemical characterization, along with a molecular modeling study, showed that the size and the polarity of the side chain at position 346 assisted substrate binding and turnover. This study shows for the first time that the amino acid at position 346 contributes to the β‐lactamase activity of cephalosporinases. Asparagine and isoleucine residues, which are well conserved at position 346 among AmpC‐type enzymes, modulate their hydrolysis spectrum in an opposing sense. Ile‐346 confers higher level of cephalosporins resistance, whereas Asn‐346 confers carbapenem resistance in combination with outer membrane impermeability.